PRESENÇA NEGRA NO ESTADO DO AMAZONAS: a contribuição dos arquivos do TJAM - Juarez Clementino da Silva Junior (TRF2, 2020)
The black presence in the Amazon has a historic denial or diminution. It happened because it belonged to another portuguese colony in the Americas, only integrated with the state of Brazil after the independence of this and also due to the characteristics of the region had different economic exploitation in relation to other regions, with much more modest use of black African enslaved work. In the second half of the nineteenth century, a portion of free and freed blacks was not reduced in the population, in addition to a drop in still enslaved people. Part of the denial, comes from the modernization brought about by the rubber boom, the city of Manaus aspired to be a "Paris of the Tropics", that cosmopolitan aspiration of the "Belle Epoque" was aligned to another, hygienist, in which the figures of the black and the indigenous peoples should be, if not physically eliminated, at least hidden. What turned out to be a popular belief of non-black presence until very recently. In recent years, the academy has turned to the deconstruction of this denial, through various postgraduate research, especially in history. Some of that research has used the historical collection from the archives of the Amazonas Court of Justice. In fact, the collection was awarded in 2018 with the UNESCO seal "Memories of the world", for the documentary set "Free Africans in the 19th century Amazonian Justice", being thefirst and only state collection to have such distinction.